Original paperShort-term clinical outcome and dosimetric comparison of tandem and ring versus tandem and ovoids intracavitary applicators - Ma, John K.; Mourad, Waleed F.; Allbright, Robert; Packianathan, Satyaseelan; Harrell, Leslie M.; Chinchar, Edmund; Nguyen, Alex; Vijayakumar, Srinivasan (Journal of Contemporary Brachytherapy, 2015)
Purpose: To compare the short-term toxicity and dosimetry of tandem and ring (TR), and tandem and ovoid (TO) applicators in treatment of gynecologic malignancy. Material and methods: Following pelvic external beam radiation therapy (EBRT), a total of 52 computed tomography-based plans from 13 patients with cervical cancer (FIGO IB2-IIIB) were evaluated for HDR brachytherapy. Prescription was 7 Gy to the ICRU point A for four weekly fractions. Gastrointestinal and genitourinary toxicities were evaluated. Clinical target volume (CTV) and organs at risk were delineated on CT scans. Bladder, rectum, and sigmoid mean doses and D2cc were calculated. Treatment time and irradiated tissue volume were compared. Percent of CTV receiving 100% (CTV100%) of the prescribed dose as well as the percent of the prescription dose covering 90% of the CTV (D90) were evaluated. Results: Gastrointestinal and genitourinary toxicities were not different between TO and TR applicators. No significant differences in the dose to the right and left point A, or the left point B were observed. TO delivered a higher dose to right point B. Organs at risk doses were similar between the two applicators, except mean rectal dose was lower for TO applicator. Overall, TO treats a larger tissue volume than TR. Mean treatment time was shorter for TR. Tumor coverage (D90 and CTV100%) was equivalent between TO and TR applicators. Conclusion: Although TO treats a larger tissue volume than TR, short-term toxicities and tumor coverage are similar. Long-term clinical outcomes will be elucidated with longer follow up period.